Lactobacillus paracasei N1115 attenuates obesity in high‐fat diet‐induced obese mice. Issue 1 (20th October 2022) - Sun, Yanan; Chen, Shanbin; Ren, Fazheng; Li, Yixuan
Abstract: Disruption of the microbial structure of intestinal bacteria due to a high‐fat diet (HFD) is closely associated with metabolic disorders, such as obesity and type 2 diabetes. Probiotics are known to modulate the gut microbiota; therefore, we demonstrated the capability of Lactobacillus paracasei N1115 ( LC ‐N1115) to attenuate obesity. Four‐week‐old male C57BL/6J mice were fed a HFD for 12 weeks to induce obesity and were then randomized to supplemented placebo or LC‐ N1115 treatment group for another 12 weeks. LC ‐N1115 treatment reduced weight gain and liver fat accumulation as well as triglyceride, total cholesterol, and low‐density lipoprotein cholesterol levels. The administration of LC ‐N1115 suppressed the expression of fatty acid synthase, interleukin‐1 β, and toll‐like receptor 4. Notably, the operational taxonomic units that negatively and positively correlated with the obesity phenotypes were enriched and reduced, respectively, in the LC ‐N1115 treatment group. These results indicate that LC ‐N1115 attenuates obesity by modulating the gut microbiota and the expression of lipid synthesis and proinflammatory cytokine genes. Abstract : Lactobacillus paracasei N1115 relieved high fat diet induced obesity. Lactobacillus paracasei N1115 decreased body weight, fat accumulation and hyperlipidemia by increasing the abundance of beneficial bacteria ( Allobaculum and L. Zeae ) and decreased harmful bacteria ( Turicibacter ).